Talent management based on therapeutic work with a professional handball team - Keczelei , Danica (Applied Studies in Agribusiness and Commerce, 2013)
All athletes regardless of their age should get mental skills development that could be integrated into their normal training. Psychological training is essential for better performance because in sports the psychological factors play a very important role. The aim of this presentation is to show the therapeutic work of a professional men’s handball team and demonstrate the nature of the social environment and how it can have an effect on their performance. The author examines how a team forms, develops and works and what factors contribute achieving the optimum performance. The functions, structures, dynamics and goals of an adult team were analyzed and on top of that the focus was on the a threemonth long therapeutic process and its results as well. In order to improve the selfawareness and team building, the players were asked to fill out following questionnaires: psychometric questionnaire of Keczeli1, Keczeli2 questionnaire about roles, tasks and responsibilities within the team and playercoach relationship and attention questionnaire (Pieron). The conclusions of this work can be useful for further talent managment and develpoment.